Mickiewicz subwersywny. Wokół projektu dziadów/Dziadów - Kuziak, Michał (Slavia Occidentalis, 2011)
The article presents Mickiewicz’s subversive project connected with the intention to exchange the old cultural centre by a new centre, designed by the author. The project evolves around Dziady (“Forefathers’ Eve”), beginning from their Vilnius-Kaunas part; the poet returns to it in his Parisian lectures. The project, based on what is provincial, is realized through the construction of tradition, being the search for power.